MOTIVATIONAL-SEMANTIC CHARACTERISTICS OF THE INDIVIDUAL TEACHERS IN THE PEDAGOGICAL COMMUNICATION - Алпатова, О. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The analysis of problems of motivation and semantic characteristics of the individual academics. It identified the most common in modern educational practice pedagogical paradigm. The peculiarities of pedagogical paradigms in the context of the professional activities of a high school teacher. The present analysis of the results of the research study of the disposition of the participants of pedagogical communication